Family influence on career decision- making Self-efficacyof students in selected senior High schools in china - GUOXIAO, KE (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to determine the family influence on career decision-making efficacy of students in select senior high schools in China. The study used standardized questionnaire, which looked into the profile of the senior high school students, their career decision-making, self-efficacy and the parents’ career behavior. Results show that the respondents came from urban areas whose parents are professionals and have high expectancy for their children to pursue careers that are economically rewarding. The students are not decisive of their career decision but their mothers are. The students from high earning families were perceived to have higher career decision-making self- efficacy than those from the average and low income parents; they are perceived to have guardians with highest career parenting behavior; being civil servants is included in their career-related activities; Parental influence was positively correlated with career-decision self-efficacy. Hence, parents should be involved in their children’s career-choice.